O solipsismo no Tractatus logico-philosophicus de Wittgensteins - Matter, Daniel (2015)
This dissertation analyzes the solipsism subject in Tractatus Logico-Philosophicus by Wittgenstein, exploring its possible interpretations and the result of each of them. While solipsism is held to be true and likely to match the realism, although it is not possible to be approached by the language with meaning, which is carried forward in the mystical and showed fields and where we encounter the metaphysical subject, the one that thinks, represents but does not exist as object alongside other objects. Since then, we will demonstrate that it is not possible for Wittgenstein to use the term solipsism in a usual manner, but in a different format, where it can be conceivable the me (solipsism) and the world (realism) simultaneously and in harmony, and the acceptance of other minds in the world. Thus being able to know the truth of solipsism through the mystical feeling.